Analysis of The Application of SAS (Structural Synthetic Analytics) Method in Initial Writing Ability in Children of Migrant Workers - Nuraini; Siti Marpuah; Ayu Wulansari; Lilis Sumaryanti; Dyah Atiiek Mustikawati; Nadia Amrul Ummah (Journal of Techno-Social, 2026)
Initial writing is a foundational literacy skill that enables children to transform oral language, visual recognition, and motor coordination into meaningful written symbols. This study analyzes the application of the Structural Analytical Synthetic (SAS) method in supporting the initial writing ability of children of migrant workers at SB At-Tanzil Kayu Ara, Malaysia. A descriptive qualitative approach was employed in Class C, involving 22 students consisting of 10 boys and 12 girls. Data were collected through classroom observation, teacher interviews, student questionnaires, and documentation, and were analyzed using the Miles and Huberman model through data collection, reduction, display, and verification. The findings show that students experienced difficulties in distinguishing similar letters, writing complete words, maintaining neatness, and constructing simple sentences. Specifically, 3 students were unable to write A-Z correctly, 10 students were unable to write words accurately, while 9 students were able to write sentences properly. The SAS method was found to be useful because it guides students from meaningful sentence structures to words, syllables, and letters before recombining them into complete forms. The study indicates that structured, contextual, and media-supported writing instruction can strengthen early literacy practices among migrant worker children in non-formal learning settings.